Fluoroscopic Stenting as a Bridge to Surgery versus Emergency Management for Malignant Obstruction of the Colon - Fan Xue; Feng Lin; Jun Zhou; Ning Feng; You-Gang Cui; Xu Zhang; Yu-Peng Yi; Wen-Zhi Liu (Emergency Medicine International)
Aim. To investigate the feasibility of a SEMS (self-expandable metallic stent) as a bridge to surgery for malignant colonic obstruction. Methods. We retrospectively reviewed 83 patients that were in accordance with inclusion criteria; of these, 33 patients that underwent fluoroscopy-guided SEMS placement followed by elective curative resection were classified as a SEMS group and 50 patients, who received emergency surgery (ES), were classified as an ES group. The clinicopathological characteristics, surgery-related parameters, complications, and three-year survival rate were compared between the two groups. Results. No significant differences between the two groups were observed in any of the clinicopathologic characteristics except for higher preoperative absolute neutrophil count in the ES group (P<0.001). Compared to the ES group, the SEMS group has significantly more cases, which featured a laparoscopic approach (72.7% vs. 14.0%, P<0.001), lower overall stoma rate (0% vs. 34.0%, P<0.001), and lower overall postoperative morbidity (27.3% vs. 56.0%, P=0.010). The oncological outcomes did not differ significantly between the two groups in terms of three-year overall survival (P=0.125). The technical and clinical success rates of stent placement were 91.7% and 100%, respectively. Conclusion. Patients treated with the stent-surgery approach had significant short-term superiorities and similar long-term outcomes, compared to patients who had emergency surgery alone. The SEMS is, therefore, safe and feasible as a bridge to surgery for malignant colonic obstruction.